Echoic survivals: Re-documenting pre-1975 Vietnamese music as historical sound/tracks of re-membering. Issue 2 (October 2020) - Nguyen, Kathy
Following the contested fall of Sài Gòn in 1975, several South Vietnamese veterans found their existence and contributions during the Việt Nam War erased. Even after 45 years of diasporic displacement, or what I refer to as the involuntary and forceful exilic removal and geographical scattering of a group due to political turnover and turmoil, the histories, stories, and legacies of South Việt Nam and the Republic of Việt Nam have largely been forgotten in the present and political landscapes of both postwar Việt Nam and the United States. Based on what I describe as a diasporic re-reading of the lyrics and re-listening of selective pre-1975 Vietnamese music, this article explores the enduring corpus of musical sounds in nhạc vàng, or pre-1975 yellow music, specifically songs that focus on war and người lính ("soldiers"). By examining its historical and spatial trajectories, I argue that Vietnamese music can be heard and described as historical sources, much of which has been overlooked in the West, that document the many erased and discounted experiences, stories, and peril of South Vietnamese veterans. As I argue, diasporic sounds echoed in Vietnamese music are crucial to understanding the history and continued peril of South Vietnamese veterans in the current geopolitical landscape. The following analysis shows that Vietnamese music contextually becomes a diasporic source for re-membering the disremembered, the forgotten, and the silenced. Vietnamese music shifts from modern music to diasporic sounds of war remembrance and loss that underscore their continued postwar plight. In this essay, I also interviewed a South Vietnamese veteran. For him, music becomes a mode of survival, representing the unfading nostalgia and memories of the Việt Nam War.